The Challenge of Distance Learning An Educator's Journey - Meagher, Michael E. (2020)
A personal narrative is presented in which the author discusses how students shifted from residential higher education to remote learning in the U.S. due to the coronavirus pandemic and how it altered the traditional professor-student relationship.
Keywords: COVID-19 pandemic; Distance Education; Teacher-student relationships